بطء التعلم -المفاهيم والخصائص- - خماد, محمد; بن خليفة, اسماعيل (جامعة الوادي - University of Eloued, 2020)
ينظر الباحثون إلى بطئي التعلم من ثلاث زوايا مختلفة، وهي: الجانب العقلي، الجانب النفسي والجانب الاجتماعي مما يترتب عليه تعريف مختلف مطابق لزاوية الرؤية. رغم هذه الاختلافات الجوهرية بين الباحثين، إلا أنهم يجمعون على التعريف التالي: بطيء التعلم هو كل طفل لا يكون قادرا على مجاراة الآخرين من زملائه في التحصيل العلمي والمعرفي، لأسباب نفسية أو اجتماعية أو عقلية. ان الاهتمام بتلك الفئة من التلاميذ يحميهم من الاحباطات الناشئة عن الفشل الدراسي، ومن اتجاهات المجتمع السلبية نحوهم، مما يجعلهم يرفضون المجتمع الذي رفضهم إما بالاعتداء أو بالانسحاب أو بالانطواء، كما أن الاهتمام بالتلميذ بطيء التعلم يعكس تكافؤ الفرص بين التلاميذ، ويشكل جانباً إيجابياً حيث يوجه طاقة بشرية لشريحة كبيرة من التلاميذ نحو الإنتاج والفاعلية الاجتماعية. الكلمات المفتاحية: بطء التعلم ؛ المفاهيم ؛ الخصائص. Slow Learning: Concepts and Characteristics Abstract: Researchers look to slow learners from three different angles, namely: the mental side, the psychological aspect and social side resulting in a different definition is identical to the angle of vision. Despite these fundamental differences between the researchers, but they agree on the following definition: a slow learning is that every child will not be able to keep up with others of his colleagues in the scientific and cognitive achievement, psychological, social or mental reasons. The interest in that category of students to protect them from the frustrations arising from academic failure, and negative trends in society towards them, causing them to reject the society that their refusal to either assault or withdraw or Balantoa, and the attention slow pupil learning reflects equal opportunities for students, and is a positive aspect where directed manpower large segment of students about the social and production efficiency.
Slow Learning: Concepts and Characteristics
مقال
Keywords: بطء التعلم ؛ المفاهيم ؛ الخصائص.; slow learning; concepts; characteristics.